2014
DOI: 10.1073/pnas.1316708111
|View full text |Cite
|
Sign up to set email alerts
|

A seismologically consistent compositional model of Earth’s core

Abstract: Earth's core is less dense than iron, and therefore it must contain "light elements," such as S, Si, O, or C. We use ab initio molecular dynamics to calculate the density and bulk sound velocity in liquid metal alloys at the pressure and temperature conditions of Earth's outer core. We compare the velocity and density for any composition in the (Fe-Ni, C, O, Si, S) system to radial seismological models and find a range of compositional models that fit the seismological data. We find no oxygen-free composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
280
2
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(321 citation statements)
references
References 39 publications
34
280
2
2
Order By: Relevance
“…however, recent experiments found that adding up to 10% of Ni does not change the hexagonal close-packed crystal structure of the solid 42 , while ab initio calculations suggest that at high T the seismic properties of Fe-Ni alloys are almost indistinguishable from those of pure iron 43 . Recent studies of core composition [44][45][46] given in section 1 of Table 1; each model is named after the corresponding molar concentration.…”
Section: Materials Properties For Earth's Corementioning
confidence: 99%
“…however, recent experiments found that adding up to 10% of Ni does not change the hexagonal close-packed crystal structure of the solid 42 , while ab initio calculations suggest that at high T the seismic properties of Fe-Ni alloys are almost indistinguishable from those of pure iron 43 . Recent studies of core composition [44][45][46] given in section 1 of Table 1; each model is named after the corresponding molar concentration.…”
Section: Materials Properties For Earth's Corementioning
confidence: 99%
“…(10) and (19)) is depicted in Fig. 3 (d); the convergence of this contribution with respect to the k-mesh density is presented in Fig.…”
Section: Anharmonic Fementioning
confidence: 99%
“…A prominent example is behavior at conditions found at the Earth's inner core. The Earth's core is composed primarily of iron, with about 10% nickel and a number of light impurities, such as sulfur, oxygen, silicon, carbon, and hydrogen that are likely to be present [10][11][12] (it has even been proposed that the "missing xenon paradox" can be explained via reactions of Xe with Fe and Ni at inner-core conditions 13 ). An outstanding problem is determination of the structure of the core materialamong other things, this knowledge can inform theories of the Earth's evolution, aid understanding of its physical features (e.g., magnetic, gravitational fields), and guide interpretation of seismological measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Even for the Earth's core, the core composition is not well-known and compositional models for the core (e.g., a silicon-versus an oxygen-bearing core) are offered as competing hypotheses (e.g., McDonough 2014). In contrast to other terrestrial bodies, compositional models for the Earth's core can be constrained by seismological data (e.g., Badro et al 2014).…”
Section: Core Compositionmentioning
confidence: 99%